A Review of Medical Oxygen Concentrators for Respiratory Applications - Erdemir, Dogan; Dincer, Ibrahim (MARY ANN LIEBERT, INC, 2025)
Medical oxygen concentrators are vital apparatuses that deliver supplemental oxygen to persons with hypoxemia. This narrative review provides a review of oxygen concentrators, outlining their operational mechanisms, classification, evaluation criteria, market accessibility, advantages, disadvantages, and prospective developments. Critical insights encompass the dominance of pressure swing adsorption technology in oxygen separation, the increasing demand for portable and energy-efficient models, and the promise of smart technologies and new materials to improve oxygen therapy. The analysis underscores the necessity of tackling issues of accessibility and cost, especially in resource-constrained environments. This review highlights the essential function of oxygen concentrators in potentially fulfilling the United Nations Sustainable Development Goals 3, 8, 12, 13, and 17 by improving health care accessibility, fostering economic growth, advancing environmental sustainability, and facilitating global partnerships. The incorporation of automated controls and artificial intelligence-driven modifications may become important for customizing oxygen administration to meet patient requirements and fluctuating conditions, hence ensuring optimal therapy and reducing the workload of health care providers. Finally, it is emphasized that the necessity of adressing issues with accessibility and cost, especially in resource-constrained environments.
Keywords: oxygen therapy; oxygen concentrators; oxygen generator; respiratory conditions; medical oxygen; General & Internal Medicine; Respiratory System